TO COMPARE THE EFFICACY OF 70 VERSUS 100 SHOCK WAVES /MINUTE OF ESWL IN MANAGING RENAL AND URETERAL CALCULI IN TERMS OF FREQUENCY OF STONE CLEARANCE - Ehsan-Ul-Haque; Amer Abbas; Mian Farrukh Imran; Naeem Ullah; Sajid Mumtaz Qazi (Journal of University Medical & Dental College, 2019)
OBJECTIVE: To compare the eﬃcacy of 70 versus 100 shock waves /minute of ESWL in managing renal and ureteral calculi in terms of frequency of stone clearance. MATERIALS AND METHODS: A Randomized Clinical Trial of Six months (12th July 2013 to 11th Jan 2014) was carried out in the Department of Urology, PIMS, Islamabad. Total 90 patients of either gender with renal or upper ureteric stones planned for shock wave lithotripsy were included. 45 patients were randomized to 70 shock waves/minute (Group I) and 45 to 100 shock waves/minute (Group II). Stone fragmentation was conﬁrmed by ﬂuoroscopy at the time of treatment, and with X-ray KUB/Ultrasonography at two weeks after post treatment. RESULTS: In group I, the treatment was eﬃcacious in 86.7% (n= 39) of patients, while in group II the percentage of such patients was 64.4% (n=29). P value found to be .014 (< 0.05). CONCLUSIONS: ESWL with 70 shock waves per minute is more eﬃcacious than 100 shock waves per minute in terms of stone free status after therapy.